ENHANCING STUDENTS’ MATHEMATICAL LOGICAL THINKING ABILITY AND SELF-REGULATED LEARNING THROUGH PROBLEM-BASED LEARNING - E. Rohaeti, Euis; A.M, Budiyanto; Sumarmo, Utari (UPI Press, 2014)
This study was intended to investigate the development of students’ mathematical logical thinking ability and self-regulated learning through Problem-based Learning (PBL). This study was a part of a master thesis and a sub-study of a Postgraduate Research Grant from DGHE in2013. This study was a pre-test-post-test quasi-experimental control group design involving 93 eleventh-grade students of a senior high school in Karawang which were chosen puposively. The instruments of this study were an essay test on mathematical logical thinking, a self-regulated learning scale, and a scale measuring students’ perception of PBL. The study revealed that students getting treatment on PBL attained better grades on mathematical logical thinking ability than students taught by conventional teaching, athough the grades were at low level. However, there was no difference in the grades for self-regulated learning between students in the two groups, although the grades were fairly good. Also, there was no correlation between mathematical logical thinking ability and self-regulated learning with students’ positive opinions toward PBL.